Keanekaragaman Makrozoobentos sebagai Bioindikator Kualitas Perairan di Ekosistem Lembur Mangrove Patikang, Kabupaten Pandeglang, Banten - Nofiyanata, Deliya; Saifullah, Saifullah; Munandar, Erik (Lembaga Teewan Journal Solutions, 2026)
Mangrove ecosystems play an important role in maintaining coastal ecological balance and supporting aquatic biodiversity. This study aimed to evaluate the water quality status of the Patikang Mangrove Ecosystem, Pandeglang Regency, Banten, based on macrozoobenthos community structure and the AZTI Marine Biotic Index (AMBI). The research was conducted in February 2025 using a descriptive quantitative approach with purposive sampling at three observation stations. Macrozoobenthos samples were collected using 1 × 1 m quadrats and identified in the laboratory. Community analysis included abundance, diversity, evenness, dominance, and AMBI calculations. The results showed that 15 macrozoobenthos species belonging to four classes were identified, with Gastropoda as the dominant group. Macrozoobenthos abundance varied among stations and sampling periods, ranging from 27.33 to 111.30 ind/m². The diversity index (H') generally indicated moderate diversity (0.658–1.448), while the evenness index (E) ranged from low to moderate (0.243–0.535). The dominance index (C) varied from moderate to high (0.318–0.616), indicating the dominance of several tolerant species. AMBI values ranged from 2.80 to 2.93, classifying all stations as slightly disturbed with good ecological status. Overall, the Patikang mangrove ecosystem remains ecologically stable, although environmental fluctuations, particularly salinity changes and rainfall, influence macrozoobenthos community structure.